Ethics of Applying Compulsory Treatment as a Preventive Measure in Criminal Law - SHEVELEVA, Svetlana; BAUMSTEIN, Anton; NOVICHKOV, Valeriy; BAYBARIN, Andrey (Journal of Advanced Research in Law and Economics, 2019)
The research discusses the debatable issue of the use of compulsory medical treatment (CMT) as a preventive measure in criminal law. CMT are measures of coercion, or more particularly, state coercion, as they are applied by state bodies on behalf of the public and are backed by the coercive power of the state. However, CMT are not a measure of responsibility. Nor are they preventive measures. The latter are an independent form of legal coercion. CMT is a preventive measure, the use of which prevents the possibility of an unlawful act without establishing guilt, i.e. assessment of the violation in terms of punishment. It is concluded that since the content of the notion of CMT can be filled with different meanings and cannot be uniquely correct and meets all the requirements of science, it must have incomplete attribution in the criminal law, which must be formal. The presentation of the author’s vision of the definition of ‘compulsory medical measures’ is preceded by the following remark. Since the content of the concept of CMT can be filled with different meanings and cannot be uniquely correct and meets all the requirements of science, so long as it should have incomplete attribution in the criminal law, be only formal. It is fundamentally impossible to encompass the general concept of CMT in the law, because it would be necessary to cite all possible definitions in this normative source. The proposed definition of CMT is only an attempt from some unusual positions to understand the essence of such a complex legal institution. And since we have defined CMT as preventive measures in criminal law, such an interpretation, in our opinion, provides an explanation for many theoretical and practical issues.